The Impact of Directly Observed Therapy of Weekly Iron Supplementation Program in Female Adolescent Hemoglobin Status - Turlina, Lilin; Rohmah, Amrina Nur (PT Inovasi Pratama Internasional, 2024)
In adolescents, nutrition is an important factor in the growth and development process, especially during the growth spurt period that occurs in early adolescence and is characterized by physical, cognitive, and reproductive organ growth and maturation of reproductive organs. Inadequate nutrition during adolescence will cause various problems, one of which is anemia. Anemia has negative impacts, including impaired growth and development, decreased learning achievement, and impaired immunity, thus increasing the occurrence of infections and reproductive disorders. This research is quasi-experimental with a one-group pretest-posttest approach. The research was conducted at Muhammadiyah I Lamongan Vocational School with a total of 44 female students. The sampling technique used in this research was total sampling. Research data analysis was carried out using the paired T-test statistical test. The results of the study showed that carrying out Directly Observed Therapy (DOT) while administering Fe tablets for 12 weeks was able to significantly increase Fe levels in adolescents, with a p-value of 0.000 (p<0.05).